2018
DOI: 10.3892/ijo.2018.4395
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of SNHG15 suppresses renal cell carcinoma proliferation and EMT by regulating the NF-κB signaling pathway

Abstract: Aberrant expression of long noncoding RNAs (lncRNAs) is associated with cancer tumorigenesis and progression. It has been suggested that lncRNAs may be potential clinical diagnostic and prognostic biomarkers, and therapeutic targets. In the present study, the expression levels of small nucleolar RNA host gene 15 (SNHG15) were significantly upregulated in renal cell carcinoma (RCC) tissues and cell lines compared with in adjacent tissues and a proximal tubule epithelial cell line, as determined by reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 29 publications
0
75
0
Order By: Relevance
“…SNHG15 is a strongly conserved lncRNA, and located on human chromosome 7p13. 11 Recently, SNHG15 has been suggested to be overexpressed in most human cancers such as lung cancer, 12,13 breast cancer, 14 hepatocellular carcinoma, 15 gastric cancer, 16 colon cancer, 17 pancreatic cancer, 18 renal cell carcinoma, 19 glioma, 20 and osteosarcoma. 21 Similarly, we also found levels of SNHG15 expression was increased in colon adenocarcinoma, rectum adenocarci- 12,13 Besides, high-expression of SNHG15 also has been found to be associated with clinical progression in gastric cancer and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG15 is a strongly conserved lncRNA, and located on human chromosome 7p13. 11 Recently, SNHG15 has been suggested to be overexpressed in most human cancers such as lung cancer, 12,13 breast cancer, 14 hepatocellular carcinoma, 15 gastric cancer, 16 colon cancer, 17 pancreatic cancer, 18 renal cell carcinoma, 19 glioma, 20 and osteosarcoma. 21 Similarly, we also found levels of SNHG15 expression was increased in colon adenocarcinoma, rectum adenocarci- 12,13 Besides, high-expression of SNHG15 also has been found to be associated with clinical progression in gastric cancer and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Small nuclear RNA host gene 15 (SNHG15) is a recently identified lncRNA and locates in chromosome 7p13. Researches showed that SNHG15 is overexpressed in gastric cancer (GC), nonsmall cell lung cancer (NSCLC) and breast cancer, and it could promote cell proliferation in these cancers . In this study, we proved that SNHG15 is up‐regulated in CRC tissues than the matched noncancerous tissues (NCTs).…”
Section: Introductionmentioning
confidence: 70%
“…In gastric cancer, SNHG15 upregulation promoted cell proliferation and invasion via modulating the expression of MMP2/MMP9 [21].In terms of lung cancer, the research of Cui et al reported that promoted SNHG15 expression enhanced tumor occurrence and development by targeting miRNA-211-3p via regulating proliferation and migration in vitro [23].Similarly in non-small cell lung cancer,two studies demonstrated that knockdown of SNHG15 could suppress tumorigenesis via inhibiting the expression of EMT,MMP2,MMP9 and regulating the miR-486/CDK14 axis [24,25]. Meanwhile, Du et al identi ed that SNHG15 facilitated renal cell carcinoma invasion and migration through involving NF-κB signaling pathway and inducing EMT process [26].With respect to breast cancer, Kong et al acknowledged that SNHG15 served as a ceRNA to sponge miR-211-3p contributing to the promotion of proliferation, migration and invasion and the inhibition of apoptosis [28].Besides, SNHG15 acted as a ceRNA to modulate miR-200a-3p/YAP1-Hippo molecular mechanism in papillary thyroid carcinoma according to the study of Wu et al [29]. Consistently, function assays revealed that upregulation of SNHG15 facilitated migration, invasion, proliferation, and chemoresistance of epithelial ovarian cancer [31].However,the throughout investigation of the signaling pathways were still insu cient in HCC,PDAC and colorectal cancer so more studies should be performed to explore the potential mechanisms of SNHG15 expression in predicting survival in diverse malignancies [22,27,30] Several highlights should be mentioned in our paper,Firstly, our meta-analysis was the rst study exhaustively investigated the association between SNHG15 expression and clinical outcomes so far.Secondly,only one random-effect model was employed in most of our analysis so the results were quite credible and accurate.Thirdly,we formulated the rigorous inclusion and exclusion criteria to select the enrolled studies for the high-quality of literatures.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, most studies have demonstrated that SNHG15 pervasively involved in gene modulation via acting as an oncogene in various malignancies and its elevated expression might be dramatically associated with prognosis and clinicopathological parameters of gastric cancer [21], hepatocellular carcinoma [22], lung cancer [23], non-small cell lung cancer [24,25], renal cell carcinoma [26], pancreatic ductal adenocarcinoma [27],breast cancer [28], papillary thyroid carcinoma [29], colorectal cancer [30] and epithelial ovarian cancer [31].…”
mentioning
confidence: 99%